2019
DOI: 10.1016/j.cell.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Degenerate Intact Sensory Afferents following Nerve Injury

Abstract: SummarySensory axons degenerate following separation from their cell body, but partial injury to peripheral nerves may leave the integrity of damaged axons preserved. We show that an endogenous ligand for the natural killer (NK) cell receptor NKG2D, Retinoic Acid Early 1 (RAE1), is re-expressed in adult dorsal root ganglion neurons following peripheral nerve injury, triggering selective degeneration of injured axons. Infiltration of cytotoxic NK cells into the sciatic nerve by extravasation occurs within 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 50 publications
2
111
0
Order By: Relevance
“…A new paradigm that emerged from our data is that motor neuron degeneration results from direct cell-to-cell contacts with NK cells, with mechanisms involving granule exocytosis and perforin expression. A recent report on a model of peripheral nerve injury, describes that the NKG2D ligand Rae1 is upregulated in the lumbar DRG of adult mice upon cutting the corresponding spinal nerve, and that neurite fragmentation is boosted by IL-2 stimulated NK cells 17 . Our data that both in CNS tissue of ALS patient and in hSOD1 G93A mice, motor neurons express different NKG2D ligands, identify NKG2D on NK cells as possible molecular targets to reduce motor neuron loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new paradigm that emerged from our data is that motor neuron degeneration results from direct cell-to-cell contacts with NK cells, with mechanisms involving granule exocytosis and perforin expression. A recent report on a model of peripheral nerve injury, describes that the NKG2D ligand Rae1 is upregulated in the lumbar DRG of adult mice upon cutting the corresponding spinal nerve, and that neurite fragmentation is boosted by IL-2 stimulated NK cells 17 . Our data that both in CNS tissue of ALS patient and in hSOD1 G93A mice, motor neurons express different NKG2D ligands, identify NKG2D on NK cells as possible molecular targets to reduce motor neuron loss.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells regulate both the adaptive and innate immune responses, and CNS infiltrating NK cells modulate neuroinflammation in neurodegenerative diseases [11][12][13][14] , and affect microglial phenotype in cerebral tumors 15,16 . In addition, it was recently described that in pathological conditions, damaged neurons express NKG2D ligands and selectively succumb to NK cell-mediated degeneration 17 . Previous longitudinal cohort studies of peripheral blood from ALS patients revealed an increased number of NK cells in patients 18 ; additionally, end-stage hSOD1 G93A mice showed high NK cell frequency in the spinal cord 19 .…”
mentioning
confidence: 99%
“…This suggests that recruitment of these immune cells to the peripheral nerve may be a key factor in driving persistent pain rather than plasticity in the transcriptomes of these cell types. This notion is supported by recent studies in rodent models (Krukowski et al, 2016;Davies et al, 2019;Yu et al, 2020) and patient transcriptional profiling (North et al, 2019). This cell-type and gene module bi-clustering approach reveals specific ligand-receptor interactions for peripheral cell types with sensory neurons that can be further mined for identification of new pain targets.…”
Section: Figure 1 Peripheral Cell Type To Sensory Neuron Interactome mentioning
confidence: 74%
“…These ECM and adhesion molecule interactions may also play a critical role in recruitment and proliferation of immune cells to peripheral nerves and the DRG after nerve injury. Insofar as these neuro-immune interactions in the periphery are emerging as key players in nerve regeneration (Davies et al, 2019) and neuropathic pain (Ji et al, 2016;Yu et al, 2020), gaining a better understanding of how this occurs will yield new insight into disease states. Therefore, this is almost certainly an area that is ripe for further exploration from the perspective of fundamental neurobiology knowledge and therapeutic target discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation